Intertextuality and Islamic Literary Narratives in Kabanti Bunga Malati from Buton, Southeast Sulawesi - Faizul Mubin, A.; Isra H, Nurul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This study explores the intertextual relationships and Islamic narratives in Kabanti Bunga Malati, a traditional oral literary work from Buton, Southeast Sulawesi. Kabanti serves as a medium for conveying religious, moral, and social values within the Butonese community. Kabanti Bunga Malati by La Ode Muhammad Nafiu offers advice on the ideal Muslim character, including the importance of humility, self-purification, self-control, and avoiding unlawful acts. This research employs a qualitative descriptive method with intertextual and hermeneutical approaches. Julia Kristeva’s theory of intertextuality is applied to understand the relationship of Kabanti Bunga Malati with other Islamic texts, such as the Qur’an, Hadith, and Sufi literature. Friedrich Schleiermacher’s hermeneutical approach is used to analyze the Islamic messages within the text, focusing on both linguistic structure and authorial intent. The primary data comes from the Kabanti Bunga Malati manuscript, while secondary data is derived from relevant books and scholarly articles. Data collection techniques include reading, note-taking, and describing key points related to the research topic. Data analysis employs content analysis, chosen for its ability to identify themes, patterns, and relevant categories from the collected data. The findings show that Kabanti Bunga Malati plays a crucial role in conveying Islamic teachings through poetic form, religious symbolism, and strong moral messages. It has a close connection with various classical Islamic texts, including the Qur’an, Hadith, Sufi literature, and other Islamic literary works. The Islamic narrative in this text emphasizes the balance between ritual and morality in daily life and highlights the importance of self-reflection as a mirror to achieve spiritual purity. These findings are expected to contribute to the study of Islamic literature in the Nusantara and enrich the understanding of the role of local literature in preserving religious teachings and cultural values in Butonese society.